The features of NiCx (x ⩽ 0.33) phase formation at the mechanochemical alloying of Ni-CNT and Ni-graphite mixtures - Nakonechna О.І.; Belyavina, N.N.; Ivanenko, K.O.; Kuryliuk, A.M.; Dusheiko, M.G.; Makara, V.A. (Reports of the National Academy of Sciences of Ukraine, 2020)
Nanoscaled NiCx carbide (x < 0.33) with a defective cubic structure of the sphalerite type (a = 0.3550) was synthesized in a high-energy ball planetary mill by the mechanical alloying of two different charges: a nickel powder and multiwalled carbon nanotubes (CNT) or a mixture of nickel and graphite powders. The features of the formation of this carbide were revealed on the basis of a complex X-ray study of synthesis products with the use of phase analysis, refinement of the crystalline structure of the phases, the determination of the micr-deformation of the crystal lattice, and residual stresses. As a result, it has been shown that carbon atoms from amorphized CNT, apparently, have a somewhat smaller effective radius than the carbon atoms from amorphous graphite. The Vickers microhardness of HP-HT compacted NiC0.33 (6.9—7.2 GPa) samples was determined. This compact material has been tested as a potential material used in the coating deposition by electron beam technology. Thin films obtained (up to 150 nm) possess a high adhesion to silicon substrate, as well as to a substrate made of fused glass, and high abrasion resistance. These coationgs are characterized by a high thermal stability in the temperature range up to 850 ºC and could be recommended for applications as heat resistant protective coatings.